Mutually reinforcing effects of genetic variants and interferon-β 1a therapy for pulmonary arterial hypertension development in multiple sclerosis patients. (September 2019) - Lerche, Marianne; Eichstaedt, Christina A.; Hinderhofer, Katrin; Grünig, Ekkehard; Tausche, Kristin; Ziemssen, Tjalf; Halank, Michael; Wirtz, Hubert; Seyfarth, Hans-Jürgen
Based on a small number of cases, interferon beta (IFN-β) has been added to the list of drugs that might induce pulmonary arterial hypertension (PAH) in the current European guidelines for the diagnosis and treatment of pulmonary hypertension. Here, we propose that multiple sclerosis patients who are genetically predisposed to PAH may be at higher risk to develop disease when treated with IFN-β. We included two patients with multiple sclerosis who developed a manifest PAH after five amd eight years on IFN-β 1a therapy, respectively (without confirmed right heart catheterization). In both patients, PAH markedly improved after discontinuation of IFN-β 1a and initiation of targeted PAH therapy. For genetic analysis, we used a PAH-gene panel based on next-generation sequencing of 16 PAH and 38 candidate genes. In one of the two patients, we could identify a nonsense variant in the PAH gene ATP13A3 . The second patient showed a missense variant of the CYP1B1 gene, which might be linked to PAH predisposition. The results of this study support the hypothesis that multiple sclerosis patients who receive IFN-β 1a therapy might be at higher risk for the development of manifest PAH, if they carry a pathogenic variant or sequence variant genetically predisposing to the disease. However, further studies are necessary to systematically investigate the presence of predisposing PAH gene variants in these patients.